Modulation the electronic structure of hollow structured CuO-NiCo2O4 nanosphere for enhanced catalytic activity towards methanolysis of ammonia borane. (15th January 2023) - Feng, Yufa; Li, Yuanzhong; Liao, Qingyu; Zhang, Weimian; Huang, Ziqi; Chen, Xin; Shao, Youxiang; Dong, Huafeng; Liu, Quanbing; Li, Hao
Graphic abstract: Highlights: High performing hollow CuO-NiCo2 O4 catalysts for NH3 BH3 methanolysis were prepared. TOF for the hollow CuO-NiCo2 O4 in NH3 BH3 methanolysis is up to 23.2 min −1 . The Co center in CuO-NiCo2 O4 is recognized as active sites by DFT calculations. Synergistic effect between CuO and NiCo2 O4 results from the electrons migration. Abstract: Rational construction of cost-efficient catalysts with high activity and durability for hydrogen production from ammonia borane (AB) methanolysis is highly desirable but remains a substantial challenge. In this work, we constructed a series of non-noble-metal based hollow CuO-NiCo2 O4 nanospheres composite, in which the CuO-NiCo2 O4 -0.8 nanospheres exhibit robust catalytic activity with a high turnover frequency (TOF) of 23.2 molH2 molcat. −1 min −1 towards AB methanolysis. Systemic experimental and computational studies reveal the promotion of activity results from the synergistic effect between CuO and NiCo2 O4 . It is revealed the combination of CuO with NiCo2 O4 caused the electrons migration among Cu, Ni and Co sites and the change of d-band centers of catalyst, thus enhancing the adsorption process of CH3 OH and AB molecules on catalyst and subsequently promoting the catalytic activity. Moreover, the Co center in CuO-NiCo2 O4 composite is recognized as active sites by DFT calculations. Mechanistically, the rate determining step is the dissociation of OH bond in CH3 OH, which is confirmed by kinetic isotopic effect experiment. A plausible mechanism of methanolytic dehydrogenation of AB on CuO-NiCo2 O4 was proposed based on experiment and DFT calculations. These findings should shed light on the rational construction of cost-efficient catalysts with high performance for hydrogen production from AB methanolysis.